OPTICALLY PUMPED (CD3OH)-C-13 - FAR-INFRARED LASER LINES AND ASSIGNMENT - Telles, E. M.; Moraes, João Carlos Silos [UNESP]; Scalabrin, A.; Pereira, D.; Carelli, G.; Ioli, N.; Moretti, A.; Strumia, F. (Institute of Electrical and Electronics Engineers (IEEE), 1994)
Fourier transform and IR optoacoustic absorption data of (CD3OH)-C-13 were used to search for new FIR laser lines. We have used a waveguide CO2 laser of 300 MHz tunability as the optical pumping source. We report the observation and characterization of 13 new lines. Three of these lines are associated with absorbing transitions appertaining to the weak (CD3)-C-13 asymmetric bending mode.